Prevalence and Patterns of Sexual Dysfunction in Male Patients Suffering from Major Depressive Disorder Attending Psychiatry Outpatient Department - Arpit Jani; Kalpesh Chandrani; Nisha Prajapati (Journal of Psychosexual Health, 2023)
Background: Major depressive disorder (MDD) can cause sexual dysfunction (SD), and it is more frequent with antidepressant treatment. Different antidepressant agents have different effects on SD according to their group and dose, which is studied in the present research. Aims: (a) To study the prevalence and patterns of SD in male patients with MDD, both drug naïve and on antidepressant treatment. (b) To correlate the severity of depression and SD. Settings and Design: Cross-sectional study carried out among 200 patients who attended to the psychiatry outpatient department of a tertiary care hospital. Materials and Methods: Every fifth patient with MDD attending to an investigator had been enrolled for the study. Sociodemographic details and clinical variables were obtained. The diagnosis of MDD established by the Diagnostic and Statistical Manual of Mental Disorders , fifth edition, criteria and the Hamilton Depression Rating Scale was used to assess the severity of depression. The Arizona Sexual Experience Scale and Change in Sexual Functioning Questionnaire-14 was applied to measure SD. Statistical Analysis: Statistical analysis was done using the χ 2 test, unpaired t test, Pearson correlation coefficient, and analysis of variance test. Results: Total 82 (41%) patients had SD. Amongst them, 37 (45.12%) patients had the onset of SD before and 45 (54.88%) patients had the onset of SD after treatment. There was a statistically significant correlation between the severity of depression and SD ( P = .001), SD responses of patients on the selective serotonin reuptake inhibitor and tricyclic antidepressant ( P = .005). Sexual pleasure shows statistical significance with severity ( P = .004) and duration of depressive illness ( P = .03). The age factor was statistically significant with SD. Conclusions: Sexual dysfunction had significance with the severity of depression. Sexual pleasure had significance with severity and duration of depression, and some SD domains had significance with age groups.